Frequentist Parameter Estimation of Two-Parameter Exponentiated Log-logistic Distribution BB - Chaudhary, Arun Kumar (NCC Journal, 2019)
In this paper, we have considered frequentist parameter estimation of two parameter exponentiated log-logistic distribution based on a complete sample. The parameters are estimated using a likelihood-based classical inferential procedure. This study has tried to compute MLEs along with their asymptotic confidence interval, contour plot and standard errors. The K-S test statistic, Quantile-Quantile (QQ) and Probability-Probability (PP) plots are used to check the validity of the model. All the computations are performed in R software. Areal data set is considered for illustration of the purposed inferential procedures.